Pandemia, envejecimiento y políticas públicas en América Latina. Apuntes teóricos para pensar el problema de las vejeces desiguales desde los enfoques del curso de vida y de la economía política del envejecimiento - Marzioni, Sofía Clarisa (2021)
The pandemic caused by the SARS-CoV-2 coronavirus highlighted the diversity and inequality among older people in Latin American countries. From what theoretical frameworks is it possible to undertake its analysis? How to do it from the specificities of the region? What is the role played by the State and public and social policies? This article arises from the conviction that it is necessary to review the analytical frameworks used to understand aging. It is proposed to problematize unequal old age by reviewing and articulating some theoretical premises of two approaches, that of the life course and that of the political economy of aging. It is argued that these allow a better grasp of the complexity of social reality, nurturing more accurate diagnoses about the situation and problems of the elderly in the region, which can serve as a starting point for the design of new policies and to question the potentialities and limits of existing ones.